The Contribution of Microbial- and Plant-Derived Carbon to Soil Organic Carbon Fractions and Stability Under Manure Application Combined with Straw Incorporation - Yunjie Wen; Xian Liu; Na Yang; Yongping Li; Jiancheng Zhang (Agronomy)
The integration of manure and straw substantially affects soil organic carbon (SOC) dynamics, transformation, and long-term stabilization in agricultural systems. Dissolved organic carbon (DOC), particulate organic carbon (POC), and mineral-associated organic carbon (MOC) are the three main components of the SOC pool, each influencing soil carbon dynamics and nutrient cycling. Current research gaps remain regarding how combined fertilization practices affect the inputs of plant-originated and microbe-derived carbon into SOC pools and stability mechanisms. Our investigation measured SOC fractions (DOC, POC, MOC), SOC mineralization rate (SCMR), microbial necromass carbon, lignin phenols, enzyme activities, and microbial phospholipid fatty acids (PLFAs) over a long-term (17 years) field experiment with four treatments: mineral fertilization alone (CF), manure-mineral combination (CM), straw-mineral application (CS), and integrated manure-straw-mineral treatment (CMS). The CMS treatment exhibited notably elevated levels of POC (7.42 g kg−1), MOC (10.7 g kg−1), and DOC (0.108 g kg−1), as well as a lower SCMR value (1.85%), compared with other fertilization treatments. Additionally, the CMS treatment stimulated the buildup of both bacterial and fungal necromass while enhancing the concentrations of ligneous biomarkers (vanillin, syringyl, and cinnamic derivatives), which correlated strongly with the elevated contents of fungal and bacterial PLFAs and heightened activity of carbon-processing enzymes (α-glucosidase, polyphenol oxidase, cellobiohydrolase, peroxidase, N-acetyl-β-D-glucosidase). Furthermore, fungal and bacterial microbial necromass carbon, together with lignin phenols, significantly contributed to shaping the composition of SOC. Through random forest analysis, we identified that the contents of bacterial and fungal necromass carbon were the key factors influencing DOC and MOC. The concentrations of syringyl phenol and cinnamyl phenols, and the syringyl-to-cinnamyl phenols ratio were the primary determinants for POC, while the fungal-to-bacterial necromass carbon ratio, as well as the concentrations of vanillyl, syringyl, and cinnamyl phenols, played a critical role in SCMR. In conclusion, the manure combined with straw incorporation not only promoted microbial growth and enzyme activity but also enhanced plant- and microbial-derived carbon inputs. Consequently, this led to an increase in the contents and stability of SOC fractions (DOC, POC, and MOC). These results suggest that manure combined with straw is a viable strategy for soil fertility due to its improvement in SOC sequestration and stability.